Alendronate enhances osseointegration in a murine implant model. Issue 4 (19th September 2020) - Vertesich, Klemens; Sosa, Branden R.; Niu, Yingzhen; Ji, Gang; Suhardi, Vincentius; Turajane, Kathleen; Mun, Sehwan; Xu, Ren; Windhager, Reinhard; Park‐Min, Kyung Hyun; Greenblatt, Matthew B.; Bostrom, Mathias P.; et al.
Abstract: Administration of bisphosphonates following total joint arthroplasty might be beneficial to reduce aseptic loosening. However, their effects on peri‐implant bone formation and bone–implant interface strength have not been investigated yet. We used a physiologically loaded mouse implant model to investigate the short‐term effects of postoperative systemic alendronate on osseointegration. A titanium implant with a rough surface was inserted in the proximal tibiae of 17‐week‐old female C57BL/6 mice ( n = 44). Postimplantation mice were given alendronate (73 μg/kg/days, n = 22) or vehicle ( n = 22) 5 days/week. At 7‐ and 14‐day postimplantation, histology and histomorphometry were conducted. At 28 days, microcomputed tomography and biomechanical testing were performed ( n = 10/group). Postoperative alendronate treatment enhanced osseointegration, increasing maximum pullout load by 45% ( p < .001) from 19.1 ± 4.5 N in the control mice to 27.6 ± 4.9 N in the treated mice, at day 28 postimplantation. Alendronate treatment increased the bone volume fraction by 139% ( p < .001) in the region distal to the implant and 60% ( p < .05) in the peri‐implant region. At 14‐day postimplantation, alendronate treatment decreased the number of osteoclasts per bone perimeter ( p < .05) and increased bone volume fraction ( p < .01) when compared with the control group. Postimplantation, short‐term alendronate treatment enhanced osseointegration as demonstrated by increased bone mass, trabecular bone thickness, and maximum pullout load. Alendronate decreased peri‐implant osteoclasts while preserving peri‐implant osteoblasts and endothelial cells, in turn, increasing bone volume fraction. This data supports the postoperative clinical use of bisphosphonates, especially in patients with high risks of aseptic loosening.